Strategi Pengembangan Masyarakat Melalui Bina Kelompok (Kasus Pengrajin Keripik Umbi Gadung di Dusun Ngerjo, Desa Joho, Kecamatan Kalidawir, Kabupaten Tulungagung, Provinsi Jawa Timur) - IKHSAN, MUKHAMAD KHOIRUL; WINDIA, I WAYAN; PUTRA, I GEDE SETIAWAN ADI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
Community Development Strategy through Community Development (Case of Gadung Tuber Chips Craftsman in Ngerjo Hamlet, Joho Village, Kalidawir District, Tulungagung Regency, East Java Province) The purpose of this study was to determine the response of craftsmen to the formation of groups for craftsmen in Ngerjo Hamlet, Joho Village, Kalidawir District, Tulungagung Regency, East Java Province and to find out the strategy of forming a group of gadung tuber chips craftsmen in Ngerjo Hamlet, Joho Village, Kalidawir District, Tulungagung Regency, East Java Province. This study uses qualitative data analysis techniques with interactive models. This research was conducted in Ngerjo Hamlet, Joho Village, Kalidawir District, Tulungagung Regency, East Java Province from May 2019 to December 2019. The data collected were analyzed using descriptive and SWOT analysis methods. The results showed that the response of craftsmen to the formation of groups for artisans in Ngerjo Hamlet, Joho Village, Kalidawir District, Tulungagung Regency, East Java Province was responded to well and interest in forming such groups of craftsmen increased after the craftsmen learned the many benefits of forming such groups as they could serve as a learning class, a vehicle for collaboration, and a vehicle to develop human development, business development, environmental development and group development itself. The results also showed that the strategy for forming groups of yam tuber chips craftsmen in Ngerjo Hamlet, Joho Village, Kalidawir District, Tulungagung Regency, East Java Province based on the results of the SWOT analysis was an aggressive strategy namely a strategy by (1) Increasing the craftsmen's awareness of the importance of the group; (2) Increasing the interest of craftsmen to create groups; and (3) initiating activities to create groups.